Estudo do uso de periódicos científicos brasileiros da área de física por docentes dos programas de pós-graduação do Nordeste - Monica Maria Machado Ribeiro Nunes de Castro (2001)
For the development of technical and scientific activities some conditions are essential, such as the guarantee of easy access to information and facility in communication among researchers, specially in some areas like physics, which use formal communication, mainly through scientific journals. Given the increasing difficulty of obtaining information, faced by scientists in general, primarily for those who are inserted in public institutions at developing countries, this study analyses the use of Brazilian scientific journals of physics by professors involved in graduate programs at Brazilian Northeast region. The population is represented by the professors working in Northeasts graduate programs, comprising 84 individuals, and the scientific journals in physics. The investigation took into consideration: 1) a list of periodicals used for publication of scientific journals articles through Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES); 2) citation of scientific journals observed in these articles, which were obtained through Web of Science; and 3) a list of scientific journals used by professors for teaching/research. Other data collected through a questionnaire were: characteristics of the professors; her needs and sources of information; general aspects related to the use of scientific journals frequency, importance, subscription, motives of use, publication of articles in Brazilian or in foreign scientific journals and difficulties for access; general importance of titles, number of published articles, motives of use, ways of access and influential factors in their use. A form was used for identification of chracteristics that could have influence the use of the most significant Brazilian scientific journals: Brazilian Journal of Physics and Revista Brasileira de Ensino de Física. In the results show that Brazilian scientific journals have a low use by professors of Northeasts graduate programs. To satisfy their information needs which are motivated mainly for the necessity of recognition by the scientific community, these professors use, primarly, foreign scientific journals especially North-American periodicals. Other conclusions related to the researched parameters are also presented in this work.